2019
DOI: 10.2106/jbjs.18.00868
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral Kinematics During Compressive Loading of the ACL-Intact and ACL-Sectioned Knee

Abstract: Background: Tibial geometry and knee laxity have been identified as risk factors for both noncontact anterior cruciate ligament (ACL) rupture and instability in the setting of ACL insufficiency via clinical studies; yet, their biomechanical relationships with tibiofemoral kinematics during compressive loading are less well understood. The purpose of this study was to identify the relative contributions of sagittal tibial slope, medial tibial eminence volume, and anterior knee laxity to tibiofemoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 62 publications
1
9
1
Order By: Relevance
“…Understanding of ACL injury risk is improved by this in vivo study that links bone and meniscus morphology to dynamic kinematics during running and drop jump. A study of 13 cadaver knees that found internal tibial rotation was positively correlated to lateral sagittal slope contradicts our results [37]. One explanation for these contrary results is that the knee was loaded with only 300 N of compression at a ixed lexion angle of 15° in that cadaver study.…”
Section: Discussioncontrasting
confidence: 99%
“…Understanding of ACL injury risk is improved by this in vivo study that links bone and meniscus morphology to dynamic kinematics during running and drop jump. A study of 13 cadaver knees that found internal tibial rotation was positively correlated to lateral sagittal slope contradicts our results [37]. One explanation for these contrary results is that the knee was loaded with only 300 N of compression at a ixed lexion angle of 15° in that cadaver study.…”
Section: Discussioncontrasting
confidence: 99%
“…One reason might be the increased translation in the lateral versus medial tibiofemoral compartment in combination with the fact that meniscal allograft bodies are fixed using sutures, limiting the mobility of the graft as compared with the native lateral meniscus. 29,41 In addition, a steep posterior tibial slope has been shown to be associated with increased anterior tibial subluxation, 11 which may increase the stress on the anterior parts of meniscal allografts. Preoperative sizing of meniscal allografts is usually based on the length and width of the corresponding tibial plateau.…”
Section: Discussionmentioning
confidence: 99%
“…15 26 27 In the setting of an ACL-insufficient knee, the MTE seems to play a larger role in tibiofemoral stability, with lower MTE volumes being correlated with increased anterior tibial translation. 15 Therefore, while ACL injuries in young patients are often treated operatively, in a subgroup of older individuals with decreased posterior tibial slopes, large MTE dimensions, and no excessive anteroposterior laxity, the increased tibiofemoral stability resulting from these geometric factors may permit successful nonoperative management. To our knowledge, this is the first study to validate a reproducible method to measure MTE height and width and compare the MTE measurements between CT and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, decreased volumes of the MTE may lead to less bony contact with the notch, placing greater demand on ligamentous restraints and other soft tissues, such as the menisci. 15,26,27 In the setting of an ACL-insufficient knee, the MTE seems to play a larger role in tibiofemoral stability, with lower MTE volumes being correlated with increased anterior tibial translation. 15 Therefore, while ACL injuries in young patients are often treated operatively, in a subgroup of older individuals with decreased posterior tibial slopes, large MTE dimensions, and no excessive anteroposterior laxity, the increased tibiofemoral stability resulting from these geometric factors may permit successful nonoperative management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation